Fabrication of three‐dimensional porous scaffolds with controlled filament orientation and large pore size via an improved E‐jetting technique. Issue 4 (24th October 2013) - Li, Jin Lan; Cai, Yan Li; Guo, Yi Lin; Fuh, Jerry Ying Hsi; Sun, Jie; Hong, Geok Soon; Lam, Ruey Na; Wong, Yoke San; Wang, Wilson; Tay, Bee Yen; Thian, Eng San
Abstract Biodegradable polymeric scaffolds have been widely used in tissue engineering as a platform for cell proliferation and subsequent tissue regeneration. Conventional microextrusion methods for three‐dimensional (3D) scaffold fabrication were limited by their low resolution. Electrospinning, a form of electrohydrodynamic (EHD) printing, is an attractive method due to its capability of fabricating high‐resolution scaffolds at the nanometer/micrometer scale level. However, the scaffold was composed of randomly orientated filaments which could not guide the cells in a specific direction. Furthermore, the pores of the electrospun scaffold were small, thus preventing cell infiltration. In this study, an alternative EHD jet printing (E‐jetting) technique has been developed and employed to fabricate 3D polycaprolactone (PCL) scaffolds with desired filament orientation and pore size. The effect of PCL solution concentration was evaluated. Results showed that solidified filaments were achieved at concentration >70% (w/v). Uniform filaments of diameter 20 μm were produced via the E‐jetting technique, and X‐ray diffraction and attenuated total reflectance Fourier transform infrared spectroscopic analyses revealed that there was no physicochemical changes toward PCL. Scaffold with a pore size of 450 μm and porosity level of 92%, was achieved. A preliminary in vitro study illustrated that live chondrocytes were attaching on the outer and inner surfaces of collagen‐coated E‐jetted PCL scaffolds. E‐jetted scaffolds increased chondrocytes extracellular matrix secretion, and newly formed matrices from chondrocytes contributed significantly to the mechanical strength of the scaffolds. All these results suggested that E‐jetting is an alternative scaffold fabrication technique, which has the capability to construct 3D scaffolds with aligned filaments and large pore sizes for tissue engineering applications. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2014:102B:651–658.